Abstract 13916: Quality of Life Measured in First-line Therapy for Paroxysmal Atrial Fibrillation: A Comparison Between Cryoballoon Catheter Ablation versus Antiarrhythmic Drug Therapy - Pavlovic, NIkola; Kuniss, Malte; Velagic, Vedran; Hermida, Jean-Sylvain; Healey, Stewart; Arena, Giuseppe; Badenco, Nicolas; Meyer, Christian; Chen, Jian; Iacopino, Saverio; Anselme, Frederic; Chierchia, Gian-Battista (Circulation (New York, N.Y.), 2020)
IntroductionThe Cryo-FIRST study (NCT01803438) demonstrated that pulmonary vein isolation (PVI) with cryoballoon catheter ablation (CA) is superior to antiarrhythmic drug (AAD) therapy as a first line treatment for the prevention of atrial arrhythmia recurrence in patients with paroxysmal atrial fibrillation (PAF). Earlier CA may also be beneficial for improving quality of life (QoL). HypothesisWe hypothesized that PVI with cyroballoon CA is superior to AAD therapy for improving QoL in treatment naïve patients with PAF. MethodsPatients with symptomatic PAF free of heart disease who had not been administered AAD therapy for >48 hours were enrolled at 18 sites in 9 countries. Patients were randomized (1:1) to cryoballoon CA (Arctic Front Advance, Medtronic) or AAD therapy (Class IC or III). Subjects were followed at 1, 3, 6, 9, and 12 months. QoL was evaluated using the Atrial Fibrillation Effect on Quality of Life (AFEQT) and SF-36 v2 questionnaires. Health domains and component scores from the SF-36 were transformed to norm-based T scores. Mean adjusted differences between arms were compared at each follow-up. ResultsOf the 218 patients randomized (age 52±13 years, 68% male) 86% completed the 12-month follow-up. Crossovers occurred in 9% of subjects (N=20, CA-to-AADN=1, AAD-to-CAN=19). There were no group differences in baseline AFEQT or SF-36 scores. The mean AFEQT summary score was more favorable in the CA vs. AAD group at 12 months (88.9 vs. 78.1 points, respectively). The adjusted difference was 9.9 points (95%CI5.5-14.2; P < .0001, Figure). A significant adjusted mean difference favoring CA was observed for the SF-36 physical component score at months 3 (1.8 points, p=0.031) and 9 (2.0 points, p=0.018). No other differences were observed in the physical or mental component scores between groups. ConclusionsCryoballoon CA was superior to AAD therapy for improving AF-specific QoL in treatment naïve patients with symptomatic PAF.